Closing the climate adaptation gap for water supply utilities - Becher, O (2023)
Resilient water supply infrastructure is fundamental for human life and wellbeing. In addition to the number of people who are not yet connected to a water utility network, millions suffer from frequent and prolonged climate-induced water supply disruptions. This problem is particularly acute in the developing world, where countries lack sufficient financing for water infrastructure maintenance and development, and where extreme climatic and hydrological variability make the challenge of designing resilient water systems even greater. The goal of this DPhil is to develop and apply a set of complementary, applied, frameworks for analysing climate risks to water supply systems to guide decision making and enable the quantification of adaptation benefits. This overarching aim is divided into three research objectives. 1) To develop a framework for analysing widespread, multi-hazard climate risks to water supply utilities. 2) To develop an approach for quantifying the costs and benefits of adaptation for both water supply utilities and their customers, including those in poverty. 3) To develop a global framework for quantifying drought risk at the utility scale, as a platform for comparing benefit-cost ratios (BCR) across multiple types of adaptation actions. The first two modelling frameworks were developed around, and applied to, a case study of the National Water Commission (NWC) in Jamaica, where water supplies are vulnerable to multiple climatic hazards and subject to frequent disruptions. As presented in chapter 4, the total annual expected disruption incurred by fluvial and pluvial flooding, extreme cyclonic wind and drought is approximated to be 5 days per year per utility customer under present conditions, with significant spatial variation in risk across the utility’s systems. This risk is projected to increase by a factor of between 2 and 2.5 when end-of-century climate scenarios are propagated through the model. Based on the flood and drought risk estimates, the costs of flood and drought risk disruptions are estimated in chapter 5 to prioritise across a portfolio of adaptation options. Of the 240 sub-systems that make up the NWC’s water supply network, about 34% would benefit from flood defences and 53% would benefit from leakage reduction to adaptation to droughts. The cumulative annual benefit that could be achieved by implementing all system optimised adaptation options is estimated to be 720 million Jamaican dollars [4.65 million USD] per year, representing a substantial saving for the utility and its customers, including low-income customers. The third framework, presented in chapter 6, is applied at the global scale to find hotspots of present-day and future drought risk under future scenarios of climate change and demand growth (namely, SSP1-2.6, SSP3-7.5, SSP5-8.0). We estimate the mean rate of unsustainable or disrupted utility supply at 15% (interquartile range, 0-26%) and project a global increase in risk of between 30-45% under future scenarios. Implementing the most cost-effective adaptation action identified per utility would mitigate additional future risk by 75-80%. However, implementing the subset of cost-effective options that generate sufficient tariff revenue to provide a benefit-cost ratio that is greater than 1 would only achieve 5-20% of this benefit. The results underline the challenge of attracting the financing required to close the climate adaptation gap for water supply utilities. Although water utilities are uniquely positioned to deliver climate adaptation services for society, offering a direct channel to protect vital services from climate extremes, efforts to close the climate adaptation gap are fraught with challenges. One challenge faced by utilities and investors lies in the coherent assessment of risk and adaptation needs in the context of multiple hazards, distributional impacts triggered by a range of disruption channels and wide-ranging possible adaptation pathways. This DPhil thesis introduces a set of interdisciplinary frameworks that can be applied at both national and global scales to support investment decision making in the water supply sector. The frameworks also serve to demonstrate the impact of investments towards climate adaptation and wider development targets, supporting the business case for adaptation investments that also respond to national development priorities. With the climate agenda rapidly gaining momentum, there is an opportunity to strengthen recognition that the utilities receive in high level dialogue on climate finance and channel greater financial flows towards closing the climate adaptation gap for water supply utilities.